PENGELOLAAN PROGRAM RASKIN DITINJAU DARI VALUE FOR MONEY AUDIT UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT (STUDI KASUS DI KELURAHAN WILAYAH SURAKARTA) - Indra Lila Kusuma; Maya Widyana Dewi (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2017)
This study aims to determine the management of Raskin program to improve the welfare of the community and management of Raskin program when viewed from the Value For Money Audit to improve the welfare of the community. This research is a descriptive qualitative research focused on one phenomenon that is chosen and want to be understood in depth by ignoring other phenomena, in this case that is management of raskin program. This study uses data analysis techniques in the form of data presentation techniques and analyzed based on economic calculation, efficiency and effectiveness. A collection of information is compiled, thus giving the possibility of drawing the conclusion of the form of presentation of qualitative data in the form of narrative text. To answer the problem formulation that is about the management of Raskin program from Value for Money Audit for the welfare of the community, the researcher uses some secondary data in the form of literature of literature derived from various sources related to the discussion that want to be studied in this research such as the report of APBD 2015 and 2016 region Surakarta, books, scientific journals, electronic media, and updated media. In addition, primary data were also obtained from interviews to Raskin recipients and Raskin managers at the Surakarta district level. The results of this study indicate that (1) Implementation of Raskin program management is in accordance with the provisions in Raskin General Guidelines, (2) Implementation of Raskin program management in terms of Value for Money Audit economics has been achieved, But when viewed from the side of Raskin program as a program from the government for alleviating the poverty of the community is clearly not going well because the funds budgeted for the community are not fully accepted by the community, (3) The implementation of Raskin program management in terms of the efficiency of Value for Money Audit has been achieved. But if we look at the side of the Raskin program, then this is considered not good because it is expected with the use of large funds it is expected that the funds can be discharged evenly to all poor families in Surakarta, (4) Implementation of Raskin program management in terms of effectiveness Value for Money Audit has been reached. Although there is still no perfect effectiveness value of any performance indicator in the management of Raskin program, because only the accuracy of price and accurate measurements are effective.